Enzymatic Functionalization of Wood as an Antifouling Strategy against the Marine Bacterium Cobetia marina - Daniel Filgueira (MDPI AG, 2021)
The protection of wood in marine environments is a major challenge due to the high sensitivity of wood to both water and marine microorganisms. Besides, the environmental regulations are pushing the industry to develop novel effective and environmentally friendly treatments to protect wood in marine environments. The present study focused on the development of a new green methodology based on the laccase-assisted grafting of lauryl gallate (LG) onto wood to improve its marine antifouling properties. Initially, the enzymatic treatment conditions (laccase dose, time of reaction, LG concentration) and the effect of the wood specie (beech, pine, and eucalyptus) were assessed by water contact angle (WCA) measurements. The surface properties of the enzymatically modified wood veneers were assessed by X-ray photoelectron spectroscopy (XPS), Fourier transform-infrared spectroscopy (FTIR). Antifouling properties of the functionalized wood veneers against marine bacterium Cobetia marina were studied by scanning electron microscopy (SEM) and protein measurements. XPS and FTIR analysis suggested the stable grafting of LG onto the surface of wood veneers after laccase-assisted treatment. WCA measurements showed that the hydrophobicity of the wood veneers significantly increased after the enzymatic treatment. Protein measurements and SEM pictures showed that enzymatically-hydrophobized wood veneers modified the pattern of bacterial attachment and remarkably reduced the bacterium colonization. Thus, the results observed in the present study confirmed the potential efficiency of laccase-assisted treatments to improve the marine antifouling properties of wood.